The influence of early selenium supplementation on trauma patients: A propensity-matched analysis - Chiu, Yu-Cheng; Liang, Chia-Ming; Chung, Chi-Hsiang; Hong, Zhi-Jie; Chien, Wu-Chien; Hsu, Sheng-Der (Frontiers in Nutrition, 2022)
Oxidative stress is involved in numerous inflammatory diseases, including trauma. Micronutrients, such as selenium (Se), which contribute to antioxidant defense, exhibit low plasma levels during critical illness. This study aimed to investigate the impact of early Se supplementation on trauma patients. A total of 6,891 trauma patients were registered at a single medical center from January 2018 to December 2021. Twenty trauma patients with Se supplemented according to the protocol were included in the study group. Subsequently, 1:5 propensity score matching analysis was introduced. These patients received 100 mcg three times a day for 5 days. The primary outcome was overall survival (OS); the secondary outcomes were hospital/intensive care unit (ICU) length of stay (LOS), serologic change, ventilator dependence days, and ventilation profile. The hospital LOS (20.0 ± 10.0 vs. 37.4 ± 42.0 days, p = 0.026) and ICU LOS (6.8 ± 3.6 vs. 13.1 ± 12.6 days, p < 0.006) were significantly shorter in the study group. In terms of serology, improvement in neutrophil, liver function, and C-reactive protein level change percentile indicated better outcomes in the study group as well as a better OS rate (100 vs. 83.7%, p = 0.042). Longer ventilator dependence was found to be an independent risk factor for mortality and pulmonary complications in 6,891 trauma patients (odds ratio [OR] = 1.262, 95% confidence interval [CI] = 1.039–1.532, p < 0.019 and OR = 1.178, 95% CI = 1.033–1.344, p = 0.015, respectively). Early Se supplementation after trauma confers positive results in terms of decreasing overall ICU LOS/hospital LOS and mortality. Organ injury, particularly hepatic insults and inflammatory status, also recovered better.